Lamna nasus - Ebert, David A.; Wintner, Sabine P.; Kyne, Peter M. (Zenodo, 2021)
Lamna nasus (Bonnaterre, 1788) Porbeagle Shark Squalus nasus Bonnaterre, 1788 (ex Pennant): 10, fig. 350, pl. 85. No known types. Based on the ‘ Porbeagle’ of Pennant, 1769: 92. Type locality: Cornwall, England, northeastern Atlantic. Local synonymy : Lamna nasus : Smith, 1949a: 49, pl. 1; Smith, 1949b: 367; Smith, 1965: 49, pl. 1; Bass et al. , 1975c: 21, fig. 9; Compagno, 1984a: 248, fig.; Bass, 1986: 100, fig. 14.4, pl. 1; Compagno et al ., 1989: 44, pl.; Compagno, 1999: 118; Compagno, 2001: 121, fig. 79; Compagno et al ., 2005: 184, fig., pl. 30; Ebert et al ., 2013 a: 232, fig., pl. 28; NPOA, 2013: 49; Ebert & Dando, 2014: 53, fig.; da Silva et al ., 2015: 247; Ebert & van Hees, 2015: 145; Compagno, 2016: 1249; Weigmann, 2016: 851. South Africa voucher material : Bass et al . (1975c) commented on a young specimen of 125 cm TL in the SAM collection (no number) caught in False Bay, April 1928. Smith (1949b) recorded one from off Knysna, but without any details. South African distribution : Southwest of Cape Town to possibly off Knysna (WC). Remarks : Uncommon off the South African mainland, but common to the south and around Prince Edwards Islands where water temperatures are below 18°C. Conservation status : VU (2019). Published as part of Ebert, David A., Wintner, Sabine P. & Kyne, Peter M., 2021, An annotated checklist of the chondrichthyans of South Africa, pp. 1-127 in Zootaxa 4947 (1) on page 45, DOI:10.11646/zootaxa.4947.1.1, http://zenodo.org/record/4614567